2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--30457
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based Best Practices for First-year Blended Learning Implementation

Abstract: is a Ph.D. candidate and sessional instructor at the University of Calgary. Her research focuses on creativity in electrical and computer engineering. Ms. Marasco is also an education specialist with EZ Robot Inc. and co-hosts The Robot Program, an educational webseries for teaching robotics through technology to thousands of students, educators, and hobbyists around the globe. Ms. Marasco speaks regularly at conferences and in the community on topics from technical work to technological impact. She has won AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 3 publications
0
11
0
3
Order By: Relevance
“…Some findings: Viewing long static videos can be boring and course overwhelming [11]. Students generally perceive the online lectures as helpful [34]. Intrinsic motivation did not impact performance in the flipped classroom [37].…”
Section: G Findingsmentioning
confidence: 96%
See 1 more Smart Citation
“…Some findings: Viewing long static videos can be boring and course overwhelming [11]. Students generally perceive the online lectures as helpful [34]. Intrinsic motivation did not impact performance in the flipped classroom [37].…”
Section: G Findingsmentioning
confidence: 96%
“…One experiment uses the results of ten different universities [19]. There are reports of units from twenty-five institutions: Arizona State University College of Technology [11], Boston College [39], Brandeis University [29] [31], Bucknell University [40], Central Michigan University [28], Clark State Community College [38], CSU Monterey Bay [14], Indiana University [22], [41], Karadeniz Technical University (Turkey) [27], [23], Nazarbayev University, Kazakhstan [35], [42], Prince of Songkla University (Thailand) [26], Qatar University [43], Science and Technology of South of Minas Gerais [44], Singapore Management University [30], St. Joseph's College of Bangalore [25], Texas A&M University at Qatar [45], Trinity University [18], [46], University of British Columbia [21], University of Calgary [33], [34], University of Hartford [47], University of Helsinki [12], University of North Carolina [12], [36], [37], University of Pittsburgh [11], University of San Diego [20] and University of Toronto [15]- [17].…”
Section: Higher Education Institutionsmentioning
confidence: 99%
“…Hui et al, 2018;Kravchenko and Cass, 2017) or focus groups (e.g, Ayres et al, 2018;Kaw et al, 2019), or in-class observation based on the action research methodology (Isomöttönen and Tirronen, 2017). Some studies also investigated the lived experiences of students through self-reported opinion or motivation questionnaires (Marasco et al, 2018;Lau et al, 2018;Lei et al, 2017;Chu, Wang and Wang, 2019 However, although mixed methods are applicable to the observation of the FC experience, the core of the data was quantitative and used to apply LA algorithms. Figure 6 presents the type of algorithm applied in the LA phase.…”
Section: Figure 3: Distribution Of Studies By Year Of Publicationmentioning
confidence: 99%
“…Twelve articles out of 49 presented similar issues, which we can decompose into the following specific problematics: Quality of engagement: several studies (e.g. Marasco et al, 2018) underlined that the measures from LA were mostly click-based, and did not evaluate the quality of students' engagement with the learning material.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation